More than 12,000 farmers in Kenya provided access to zoonotic disease information though mobile phones - CGIAR Research Program on Agriculture for Nutrition and Health (2019)
Since 2017, ILRI researchers supported by A4NH have been partnering with Green Dream Tech to integrate information on 15 key zoonoses into iCow, a mobile phone agricultural platform reaching nearly 600,000 smallholder farmer subscribers in East Africa. As of November 2019, around 178,000 SMS messages on zoonotic diseases have been sent to 12,643 farmers primarily in Kenya.